Structural and functional stabilization of phage particles in carbohydrate matrices for bacterial biosensing - Balcão, Victor (2019)
Infections associated with health care services are nowadays widespread and, associated to the progressive emergence of microorganisms resistant to conventional chemical antibiotics, are major causes of morbidity and mortality. One of the most representative microorganisms in this scenario is the bacterium Pseudomonas aeruginosa, which alone is responsible for ca. 13-15% of all nosocomial infections. Bacteriophages have been reported as a potentially useful tool in the diagnosis of bacterial diseases, since they specifically recognize and lyse bacterial isolates thus confirming the presence of viable cells. In the present research effort, immobilization of these biological (although metabolically inert) entities was achieved via entrapment within (optimized) porous (bio)polymeric matrices of alginate and agar, aiming at their full structural and functional stabilization. Such phage-impregnated polymeric matrices are intended for future use as chromogenic hydrogels sensitive to color changes evolving from reaction with (released) intracytoplasmatic moieties, as a detection kit for P. aeruginosa cells.